Operationalization of Social Sustainability in the Construction Industry from a Client Perspective, How the concept of social sustainability in the construction industry is defined and communicated by Skanska’s proposed clients? - MIREÉ, ISLAM; TORYALAY, ABDURRAHMAN (My University, 2016)
Today’s construction industry is one of the highly impacting industries on the society in all three dimensions of sustainability; environmental, economic and social. Since a few years ago, sustainability within the construction industry has been a significant issue recognised by both industries professional and academicians. However, most of existing sustainability studies in construction as well as efforts of achieving sustainable built environments have extensively been focused on environmental and economic aspects, hence little achievements have been done in social terms. This thesis aims to investigate how different clients within the construction industry operationalise the concept by exploring their definitions of social sustainability and their input and actions in the context of social sustainability. A qualitative approach was adopted in order to collect empirical data, where interviews with three different actors; politicians, public clients and private clients formed the basis for data collection. The result clearly shows that the majority of all interviewed organisations are not able to give one common or universal definition of the concept, rather each organisation define the concept based on their own contribution towards achieving social sustainability. The fact that social sustainability is a multifaceted concept and can be defined context dependent, was reflected during the acquired interviews. Based on the existing literature, the authors compiled various social sustainability criteria that are taken into account at various stages of the project life cycle. The data acquired from the interviews was analysed based on the compiled social sustainability criteria model. The results and the analysis of the data showed that most of the identified social sustainability criteria are considered by the interviewed clients, regardless of expressing them as social sustainability criteria. The maturity of the interviewed organisations indicates their current status in operationalizing the concept. Assessing the maturity was based on two main factors, the frequency of criteria taken into account and the experience in communicating social sustainability requirements in procurement. The maturity of the interviewed organisations appeared to be relatively medium. However, the organisations who communicated social sustainability with other stakeholders by setting social sustainability requirements in procurement appeared to be more mature. Although some of the interviewed clients turned out to be mature on individual level in terms of having internal policies and well understanding of the concept, we still observed that communicating social sustainability on inter-organisational level is as important as on intra-organisational level.
Keywords: Samhällsbyggnadsteknik; Civil Engineering